8-Arylnaphthyl substituent retarding chain transfer in insertion polymerization with unsymmetrical α-diimine systems. Issue 45 (4th November 2020) - Li, Shuaikang; Dai, Shengyu
Abstract : The 8-arylnaphthyl substituent is highly effective for retarding the chain transfer process during ethylene (co)polymerization due to the appropriate aryl orientation. Abstract : Late transition metal olefin polymerization catalysts based on the imine structure are usually constructed with bulky arylamines as the basic unit. In this contribution, a flexible compact alkyl amine and a series of rigid bulky anilines were introduced into the α-diimine catalytic system at the same time. Thus, a series of unsymmetrical α-diimine ligands bearing an n -butyl moiety and diarylmethyl or 8-arylnaphthyl moiety as well as the corresponding nickel and palladium complexes were designed, synthesized and characterized. These unsymmetrical α-diimine nickel and palladium complexes were investigated for ethylene polymerization and copolymerization with methyl acrylate (MA). Under the synergistic effect of compact alkyl substituents and bulky aryl substituents, the nickel complexes showed moderate to high activities and generated low to high molecular weight polyethylene with various branching densities. Similar polymerization results were also observed in the corresponding palladium system. The aryl orientation in rigid bulky aryl substituents has significant effects on the polymerizations and copolymerizations in terms of activity, the molecular weight of the obtained polyethylene and copolymer, and the incorporation ratio of MA.